2017
DOI: 10.3390/ma10121411
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-Flow Production of Injectable Liposomes via a Microfluidic Approach

Abstract: Injectable liposomes are characterized by a suitable size and unique lipid mixtures, which require time-consuming and nonstraightforward production processes. The complexity of the manufacturing methods may affect liposome solubility, the phase transition temperatures of the membranes, the average particle size, and the associated particle size distribution, with a possible impact on the drug encapsulation and release. By leveraging the precise steady-state control over the mixing of miscible liquids and a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 25 publications
3
38
0
3
Order By: Relevance
“…Both these increments were more pronounced at concentrations >100 mM. These findings confirm the observations reported above (see Figure 2 ), and are also consistent with other studies describing the production of liposomes by microfluidic approaches [ 23 , 56 ]. Increasing the initial concentration of lipids likely resulted in a greater number density of lipid molecules available to form supramolecular aggregates of larger size and broader size distribution.…”
Section: Resultssupporting
confidence: 93%
“…Both these increments were more pronounced at concentrations >100 mM. These findings confirm the observations reported above (see Figure 2 ), and are also consistent with other studies describing the production of liposomes by microfluidic approaches [ 23 , 56 ]. Increasing the initial concentration of lipids likely resulted in a greater number density of lipid molecules available to form supramolecular aggregates of larger size and broader size distribution.…”
Section: Resultssupporting
confidence: 93%
“…Amongst these, vesicle size is particularly important given its impact on biodistribution, which is a key feature in the ability of liposomes to improve drug delivery, enhance efficacy and reduce off target toxicity. It is widely reported that critical process parameters that influence the size of nanoparticles produced via microfluidics include the micromixer design (e.g., [30]) and the rate of mixing (e.g., [13,16,17,31]). Within this study, we demonstrated that solvent selection was also a critical process parameter in the manufacture of liposomes using microfluidics as it could impact on particle size.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of the aqueous medium as a non-solvent is essential to the formation of liposomes by nanoprecipitation, inevitably leads to dilution of the initial lipid solution. In SHM, chaotic advection provided by herringbone grooves allows preparation of homogenous liposomes at high flow rates (in mL/min) and unprecedently low FRR (typically 1 to 5, with final lipid concentration in mM range) (Stroock, 2002), in comparison to MHF devices with typical value of TFR in µL/min range and FRR > 10 ( Hood et al, 2014;Jahn et al, 2007;Zizzari et al, 2017;Zook and Vreeland, 2010). Here we have demonstrated by increasing initial lipid concentration, with respect to the optimised FRR for each formulation (up to 30 mM), we could obtain a final lipid concentration of 7.5 mM, comparable to the liposome concentration obtained with thin film hydration method (Pereira et al, 2016).…”
Section: [Lipid Concentration Effect]mentioning
confidence: 99%
“…Despite the high demands for sterically stabilised drug delivery systems, most existing microfluidics studies (not limited to SHM) reported the production of non-PEGylated formulations (Forbes et al, 2019;Guimarães Sá Correia et al, 2017;Kastner et al, 2015;Maeki et al, 2015;Zhigaltsev et al, 2012). Few studies reported the preparation of PEGylated liposomes, which were either very small in size (~50 nm), unstable or of high dispersity (> 0.2) (Dong et al, 2017;Hood et al, 2014;Ran et al, 2016;Zheng and Fyles, 2018;Zhigaltsev et al, 2015;Zizzari et al, 2017). For instance, Zhigaltsev et al failed to produce stable and monodispersed, high phase-transition liposomes (DPPC or HSPC) using SHM microfluidics, and mixing with unsaturated lipids was needed to enhance the stability of these PEGylated liposomes (Zhigaltsev et al, 2015).…”
Section: Introductionmentioning
confidence: 99%